EKSPLORASI FAKTOR RISIKO HIPERTENSI PADA WANITA DI SEKITAR PELABUHAN - Meitha Ayu; yustini ardillah (UNUSA Press, 2022)
Harbor noise intensity remains environmental health issues causing some adverse health effect such as physiological disturbances that can lead to hypertension. This study aimed to explore the risk factors for hypertension among housewife around the harbor. It was a analytical study with cross-sectional approach. There were 90 housewives recruited around harbor Residence they were selected through simple random sampling. Data was collected through interview and blood pressure measurement. Measurement of noise intensity used Sound Level Meter and carried out at ten locations with a radius of every location was 100 meters from the harbor. Data was analyzed by univariate and bivariate using Chi-Square. This study found that the average of noise intensity in 24 hours measurement (LDN) was 57.79 dB(A) which was exceed the threshold limit value for residential area. It showed that 54.4% of housewives who live around harbor Residence got hypertension. According to statistical analysis, there was orrelation between Boom Baru Harbor noise to the risk of hypertension on women who live around harbor Residence (p-value=0.026). Besides that, another factor correlated to hypertension were age (p-value = 0.001) and the distance of house to harbor (p-value = 0.001). this study conclude that the harbor noise intensity was significantly related to hypertension.